Spanish-English Editing Model for Writing (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
The focus of this study is to show the 6 + 1 traits of the editing model for writing developed by Ruth Culman. The problem focuses on the deficient level of writing that students have, who enter Universidad de Santiago through inclusive channels (Ranking 850, PACE and Preparation Course). The objective of this study is to propose the implementation of an the editing model mentioned before for academic writing in English and Spanish, providing useful writing tools in the area of reading and writing of PAIEP at USACH.